Cu(OAc)2·H2O-promoted tandem β-alkynyl elimination of α- or β-hydroxy propargylic alcohols and homocoupling of the resulting alkynyl species. (1st September 2013) - Xu, Xiangsheng; Huang, Zhenyong; Lu, Yanfeng
Α or β-hydroxy propargylic alcohols undergo tandem C(sp)–C(sp3) bond cleavage via β-alkynyl elimination and homo-coupling of the resulted alkynyl species in the presence of Cu(OAc)2·H2O to produce the corresponding hydroxycarbonyl compounds and 1, 3-butadiynes.